Analisis Kualitas Jalur Pedestrian Di Koridor Jalan Pb Sudirman Kecamatan Pare Kabupaten Kediri - Muhammad Adib Sulaiman; Diah Intan Kusumodewi (Teknik PWK (Perencanaan Wilayah Kota), 2021)
Pedestrians are the most vulnerable road users compared to other road users. To create a pleasant walking environment, we need an environment that can provide security for pedestrians. One of the busy pedestrian lanes is the PB Sudirman Corridor area, Pare District which is a commercial area in Kediri Regency. The purpose of this study is to see how safe a path for micro scale pedestrians can then be used as input in the process of improving lane design. The method used in this study is the Pedestrian Environmental Quality Index (PEQI) method that assesses the quality of pedestrian pathways with five variables namely crossing safety; traffic; pedestrian track design; land use; and Safety and walkability variables. The results showed that the quality of pedestrian lanes in PB Sudirman Road Corridor Area has an inadequate quality average at the intersection and only has basic facilities for pedestrians on the lane, so efforts are needed to improve the quality of pedestrian lanes.